Expression and prognostic value of soluble CD97 and its ligand CD55 in intrahepatic cholangiocarcinoma - Ze-Wu Meng; Min-Chao Liu; Hai-Jie Hong; Qiang Du; Yan-Ling Chen (Tumor Biology)
The incidence rate of intrahepatic cholangiocarcinoma is rising, and treatment options are limited. Therefore, new biological markers of intrahepatic cholangiocarcinoma are needed. Immunohistochemistry and enzyme-linked immunosorbent assay were applied to analyze the expressions of CD97, CD55, and soluble CD97 in 71 patients with intrahepatic cholangiocarcinoma and 10 patients with hepatolithiasis. CD97 and CD55 were not expressed in hepatolithiatic tissues, but positive expression was observed in 76.1% (54/71) and 70.4% (50/71) of intrahepatic cholangiocarcinoma patients. The univariate analyses indicated that the positive expressions of CD97 and CD55 were related to short intrahepatic cholangiocarcinoma survival of patients (both p = 0.001). Furthermore, CD97 and CD55 expressions and biliary soluble CD97 levels were significantly associated with histological grade (p = 0.004, 0.002, and 0.012, respectively), lymph node metastases (p = 0.020, 0.038, and 0.001, respectively), and venous invasion (p = 0.003, 0.002, and 0.001, respectively). The multivariate analyses indicated that lymph node metastases (hazard ratio: 2.407, p = 0.003), positive CD55 expression (hazard ratio: 4.096, p = 0.003), and biliary soluble CD97 levels (hazard ratio: 2.434, p = 0.002) were independent risk factors for the intrahepatic cholangiocarcinoma survival. The receiver operating characteristic (ROC) curve analysis indicated that when the cutoff values of biliary soluble CD97 were 1.15 U/mL, the diagnostic value for predicting lymph node metastasis had a sensitivity of 87.5% and a specificity of 51.3%. For intrahepatic cholangiocarcinoma patient death within 60 months at a cutoff value of 0.940 U/mL, the diagnostic value sensitivity was 89.3% and the specificity was 93.3%. Biliary soluble CD97 may be a new biological marker for early diagnosis, prediction of lymph node metastasis and poor prognosis, and discovery of a therapeutic target.